Cardiovascular events in patients with atherothrombotic disease: a population-based longitudinal study in Taiwan. - Wen-Hsien Lee; Po-Chao Hsu; Chun-Yuan Chu; Ho-Ming Su; Chee-Siong Lee; Hsueh-Wei Yen; Tsung-Hsien Lin; Wen-Chol Voon; Wen-Ter Lai; Sheng-Hsiung Sheu (PLoS ONE, 2014)
BACKGROUND: Atherothrombotic diseases including cerebrovascular disease (CVD), coronary artery disease (CAD), and peripheral arterial disease (PAD), contribute to the major causes of death in the world. Although several studies showed the association between polyvascular disease and poor cardiovascular (CV) outcomes in Asian population, there was no large-scale study to validate this relationship in this population. METHODS AND RESULTS: This retrospective cohort study included patients with a diagnosis of CVD, CAD, or PAD from the database contained in the Taiwan National Health Insurance Bureau during 2001-2004. A total of 19954 patients were enrolled in this study. The atherothrombotic disease score was defined according to the number of atherothrombotic disease. The study endpoints included acute coronary syndrome (ACS), all strokes, vascular procedures, in hospital mortality, and so on. The event rate of ischemic stroke (18.2%) was higher than that of acute myocardial infarction (5.7%) in our patients (P = 0.0006). In the multivariate Cox regression analyses, the adjusted hazard ratios (HRs) of each increment of atherothrombotic disease score in predicting ACS, all strokes, vascular procedures, and in hospital mortality were 1.41, 1.66, 1.30, and 1.14, respectively (P≦0.0169). CONCLUSIONS: This large population-based longitudinal study in patients with atherothrombotic disease demonstrated the risk of subsequent ischemic stroke was higher than that of subsequent AMI. In addition, the subsequent adverse CV events including ACS, all stroke, vascular procedures, and in hospital mortality were progressively increased as the increase of atherothrombotic disease score.